2022
DOI: 10.3389/fmats.2022.930056
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation on Pavement Performance of Basalt Fiber-Reinforced Asphalt Mixture Under the Coupling Effect of Freeze-Thaw Cycles and Aging

Abstract: Due to the significant temperature difference and high solar radiation in high-altitude areas, the asphalt pavement has been in freeze-thaw cycles and radiation service conditions for a long time, resulting in a shorter service life. To extend the service life of asphalt pavement in high-altitude areas, this study uses basalt fiber to toughen the asphalt mixture, and the service characteristics of the asphalt pavement under the coupled effects of freeze-thaw cycles and aging were evaluated. First, the freeze-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Basalt fiber is an economical and environmentally friendly inorganic material that has high tensile strength, chemical stability, and great resistance to temperature, corrosion, alkalies, and acids. Relevant literature has confirmed that compared with ordinary asphalt concrete and other types of fiber asphalt concrete, basalt fiber asphalt concrete has excellent high-and lowtemperature performance, water stability, and fatigue resistance; the incorporation of basalt fiber can significantly improve the road performance of an asphalt mixture (Guo et al, 2021;Wu et al, 2022a;Cheng et al, 2022;Hui et al, 2022;Liang et al, 2022). Hence, it has been widely used to stabilize the mechanical properties of asphalt concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Basalt fiber is an economical and environmentally friendly inorganic material that has high tensile strength, chemical stability, and great resistance to temperature, corrosion, alkalies, and acids. Relevant literature has confirmed that compared with ordinary asphalt concrete and other types of fiber asphalt concrete, basalt fiber asphalt concrete has excellent high-and lowtemperature performance, water stability, and fatigue resistance; the incorporation of basalt fiber can significantly improve the road performance of an asphalt mixture (Guo et al, 2021;Wu et al, 2022a;Cheng et al, 2022;Hui et al, 2022;Liang et al, 2022). Hence, it has been widely used to stabilize the mechanical properties of asphalt concrete.…”
Section: Introductionmentioning
confidence: 99%